Impact and Management of COVID-19 Among Healthcare Workers in Two Acute Care Hospitals and Two Associated Long-term Care Centres in Barcelona, Spain. Issue 9 (September 2021) - Montero-Moraga, Jose Maria; Buron, Andrea; Sala, Maria; Santia, Paula; Lupia, Martina; Beltrán, Ana; Villar, Rocío; Horcajada, Juan Pablo; Castells, Xavier; Gil, Oscar Díaz; León, Eduardo Padilla; Serra, Consol
Abstract : Objective: To describe the characteristics of COVID-19-related episodes in healthcare workers (HCW) of two hospitals. Methods: Prospective study of HCW with COVID-like symptoms and/or who were close contacts of confirmed COVID-19. The percentage of positive PCRs among those with symptoms was calculated, and symptom's positive predictive value and negative predictive value. The characteristics of contacts were described, as well as the secondary clinical attack rate. Results: We registered 1222 episodes of HCW with COVID-like symptoms; 340 (27.8%) had a positive PCR. In 885 episodes, a HCW was a close contact of a confirmed case. In 45.5% of these, the HCW had contact with another HCW. The secondary clinical attack rate of contacts of HCW was 14.5%. Conclusion: We found a high prevalence of disease and transmission between HCW during the first wave of the SARS-CoV-2 pandemic. Abstract : Supplemental Digital Content is available in the text